Izvajanje pouka tehnike in tehnologije ter izbirnih predmetov kot ena izmed priložnosti medpredmetnega povezovanja - Pešaković, Dragica (Revija za elementarno izobraževanje, 2010)
Teaching crafts and technology and elective courses as a possibility for inter-subject cooperation. Cross-curricular integration is certainly one of the forms of modern teaching nowadays. Some of the aims of modern schooling already demand a coordinated planning of interaction between teachers of different subjects and areas. Integration is often dealt with only on the level of teaching topics, not teaching methods. For the research we integrated the subject Crafts and Technology with Chemistry, Physics and the optional subject – Handling of Metal. The teaching was carried out in teamwork, where my colleague and me complemented each other’s knowledge, professional expertise and skills. We wanted our students to integrate their knowledge about metals and nonmetals in joined activities in different school subjects, to learn the contents in its wholeness and gain a more permanent knowledge of greater quality. The students first got to know the qualities of metals through experimental work, information seeking, problem solving and cooperative learning, which then they then used in lessons on how to manufacture a metal product. They showed great interest for this kind of lesson form and were more motivated, resourceful, creative and independent than usual. They combined their knowledge into a whole, which is the purpose of cross-curriculum integration. They also gained knowledge in a broader and more practical way. The test lesson we prepared can be repeated and enhanced or transferred and adapted to new situations and other subjects.